International Society for sexual medicine's guidelines for the diagnosis and treatment of premature ejaculation - Althof, S.E.; Abdo, C.H.N.; Dean, J.; Hackett, G.; McCabe, M.; McMahon, C.G.; Rosen, R.C.; Sadovsky, R.; Waldinger, M.; Becher, E.; Broderick, G.A.; Buvat, J.; et al. (Wiley-Blackwell, 2010)
Introduction. Over the past 20 years our knowledge of premature ejaculation (PE) has significantly advanced. Specifically, we have witnessed substantial progress in understanding the physiology of ejaculation, clarifying the real prevalence of PE in population-based studies, reconceptualizing the definition and diagnostic criterion of the disorder, assessing the psychosocial impact on patients and partners, designing validated diagnostic and outcome measures, proposing new pharmacologic strategies and examining the efficacy, safety and satisfaction of these new and established therapies. Given the abundance of high level research it seemed like an opportune time for the International Society for Sexual Medicine (ISSM) to promulgate an evidenced-based, comprehensive and practical set of clinical guidelines for the diagnosis and treatment of PE. Aim. Develop clearly worded, practical, evidenced-based recommendations for the diagnosis and treatment of PE for family practice clinicians as well as sexual medicine experts. Method. Review of the literature. Results. This article contains the report of the ISSM PE Guidelines Committee. It affirms the ISSM definition of PE and suggests that the prevalence is considerably lower than previously thought. Evidence-based data regarding biological and psychological etiology of PE are presented, as is population-based statistics on normal ejaculatory latency. Brief assessment procedures are delineated and validated diagnostic and treatment questionnaires are reviewed. Finally, the best practices treatment recommendations are presented to guide clinicians, both familiar and unfamiliar with PE, in facilitating treatment of their patients. Conclusion. Development of guidelines is an evolutionary process that continually reviews data and incorporates the best new research. We expect that ongoing research will lead to a more complete understanding of the pathophysiology as well as new efficacious and safe treatments for this sexual dysfunction. Therefore, it is strongly recommended that these guidelines be re-evaluated and updated by the ISSM every 4 years. Althof SE, Abdo CHN, Dean J, Hackett G, McCabe M, McMahon CG, Rosen RC, Sadovsky R, Waldinger M, Becher E, Broderick GA, Buvat J, Goldstein I, El-Meliegy AI, Giuliano F, Hellstrom WJG, Incrocci L, Jannini EA, Park K, Parish S, Porst H, Rowland D, Segraves R, Sharlip I, Simonelli C, and Tan HM. International Society for Sexual Medicine's guidelines for the diagnosis and treatment of premature ejaculation. J Sex Med 2010;7:2947-2969.